Spent coffee grounds influence on Pleurotus ostreatus production, composition, fatty acid profile, and lignocellulose biodegradation capacity. Issue 1 (1st January 2021) - A. Alsanad, Mohammed; Sassine, Youssef N.; El Sebaaly, Zeina; Abou Fayssal, Sami
ABSTRACT: The capacity of Pleurotus ostreatus to degrade the lignocellulose of spent coffee grounds (SCG) and its resultant nutrient composition is not yet studied. The study tested four SCG/wheat straw mixtures, containing 0, 33, 67, or 100% SCG. Initial lignin content was higher, and lignin loss was lower in mixtures containing SCG, compared to control revealing lower substrate degradation. Biological yield was negatively correlated with initial lignin content, and positively with the lignin loss from substrates. The nutritional value of mushrooms was improved by a general increase in carbohydrates, a decrease in sodium content with 33% and 67% SCG, and lower fat content with 33% SCG. Polyunsaturated fatty acids of mushrooms (PUFA) increased with 67% SCG; while saturated ones (SFA) increased with 33 and 67% SCG. All mushrooms had a close PUFA/SFA, ranging between 7.4 and 8.1. The study suggests using SCG as a nutritional supplement to the commercial wheat straw. Graphical abstract: